2012
DOI: 10.1007/s10903-012-9745-9
|View full text |Cite
|
Sign up to set email alerts
|

What We Know and Don’t Know About Mental Health Problems Among Immigrants in Norway

Abstract: Mental health problems have been regarded as one of the main public health challenges of immigrants in several countries. Understanding and generating research-based knowledge on immigrant health problems is highly relevant for planning preventive interventions, as well as guiding social and policy actions. This review aims to map the available knowledge on immigrants' mental health status and its associated risk factors in Norway. The reviewed literature about mental health problems among immigrant population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 31 publications
1
86
2
1
Order By: Relevance
“…[16][17][18][19] However, it is inconsistent with international data on migrants' mental health, which shows higher risk among migrants, though these results may not be generalizable to Canada per se. 4,15 Our analyses revealed that participants who had recently migrated to Canada, within 5 years, had better mental health scores than those who had migrated to Canada more than 10 years before. Prior studies have shown that within about 10 years of living in Canada, migrant health deteriorates and converges to Canadian-born levels of mental health.…”
Section: Migration and Mental Healthmentioning
confidence: 73%
See 1 more Smart Citation
“…[16][17][18][19] However, it is inconsistent with international data on migrants' mental health, which shows higher risk among migrants, though these results may not be generalizable to Canada per se. 4,15 Our analyses revealed that participants who had recently migrated to Canada, within 5 years, had better mental health scores than those who had migrated to Canada more than 10 years before. Prior studies have shown that within about 10 years of living in Canada, migrant health deteriorates and converges to Canadian-born levels of mental health.…”
Section: Migration and Mental Healthmentioning
confidence: 73%
“…3 This extends beyond physical health indicators to encompass the mental health of immigrants in destination countries. 4 However, evidence suggests that migrants' health deteriorates after some time in host societies. 5 Diverse social determinants of health are implicated in migrant mental health disparities in Canada.…”
mentioning
confidence: 99%
“…According to Lie (2003), refugees carry "a triple burden of trauma, uprooting and settlement". While traumatic experiences and multiple negative life events in the past present a burden to many refugees, their current life situation also often adds to the health challenges they face; especially factors such as acculturative stress, discrimination, poor social support and poor socioeconomic conditions (Abebe et al, 2014) . Teodorescu, Heir, Hauff, Wentzel-Larsen, and Lien (2012, p. 316) suggest a "cumulative relationship between pre-resettlement traumas and postresettlement stressors in the mental health of refugees".…”
Section: Background: Young Cross-cultural Livesmentioning
confidence: 99%
“…There are certainly gaps and methodological challenges in this field, and the need for differentiation between groups and individuals with different cross-cultural backgrounds adds further complexity (Chuang & Moreno, 2011;Salole, 2013). Still, based on the knowledge available, several researchers recommend preventive interventions to strengthen the mental health of immigrants (Abebe et al, 2014;Chuang & Moreno, 2011), including the cross-cultural "children of migration" in focus here. Vol.…”
Section: Background: Young Cross-cultural Livesmentioning
confidence: 99%
“…Although the evidence involving emotional distress among immigrant adolescents in Norway is mixed, most studies suggest that immigrant youth are more likely to report higher levels of emotional problems than their ethnic Norwegian peers, although the magnitude of the difference in some studies is small (28). Other studies have stressed the differences in levels of emotional problems across ethnic minority groups (12;29;30).…”
Section: Different Ethnic Groups Of Preadolescents In Norwaymentioning
confidence: 99%